Pendampingan Laporan keuangan Bagi Kelompok Usaha Budidaya Ikan Air Tawar Desa Pematang Rambai : Assistance with financial reports for Pematang Village Freshwater Fish Cultivation Business Group Rambai - Mahary, Azizah; Suriono, Hadi; Rahman, Abdul (Yayasan Sagita Akademia Maju, 2024)
Freshwater fish cultivation is a promising business prospect to be developed in Batu Bara Regency. One of the cultivator groups that is active in fish production is